Benson Relaxation Technique on the Stress in the Elderly at the Neglected Social Service Center of Senja Cerah in Manado - Kristine Dareda; Dian P Iman; Hestinola Teapon (Jurnal EduHealth, 2023)
According to the World Health Organization, there are 450 million people in the world experiencing stress. Stress that occurs in the elderly is caused by a cause of stressors, namely in the form of various physical or changes in the life of the elderly in the form of both mental and social changes. Benson relaxation can have a positive impact on reducing stress through relaxation therapy. The purpose of this study was to determine the effect of the Benson Relaxation Technique on Stress Levels in the Elderly at the Senjah Cerah Abandoned Elderly Social Service Center in Manado City. Research conducted using. The research method is Quasi Experimental Design with an experimental one group pretest-posttest design. Samples were taken based on the number of respondents as many as 15 people using non-probability sampling. Data collection was carried out by means of a questionnaire. Furthermore, the collected data was processed using the SPSS version 16.0 computer program for analysis using the Wilcoxon statistical test with a significance level (α) 0 , 05. The results showed that the highest age frequency was 75-90 years 8 respondents (53.3%), the most sex was female 12 respondents (80.0%), the most length of stay was 7-10 years 7 respondents (46.7%) From the Wilcoxon test results, the value P Value = 0.002 with a significance <0.05. The conclusion in this study is the influence of the Benson Relaxation Technique on Stress Levels in the Elderly at the Senjah Cerah Derelict Elderly Social Service Center in Manado City. Suggestions are expected to increase family visits to the elderly in guest houses